Central-to-peripheral blood pressure amplification: role of the recording site, technology, analysis approach, and calibration scheme in invasive and non-invasive data agreement - Zócalo, Yanina; Bia, Daniel; Sánchez, Ramiro; Lev, Gustavo; Mendiz, Oscar; Ramirez, Agustín; Cabrera-Fischer, Edmundo I. (Frontiers in Cardiovascular Medicine, 2023)
Background: Systolic and pulse pressure amplification (SBPA, PPA) have independent ability to predict cardiovascular damage and mortality. The non-invasive estimation of SBPA and/or PPA is achieved by a great multiplicity of approaches. The most accurate non-invasive method for obtaining SBPA and/or PPA is not well defined. Aim: To evaluate the agreement between SBPA and PPA values invasively and non-invasively obtained using different: (1) measurement sites (radial, brachial, carotid), (2) measuring techniques (tonometry, oscilometry/plethysmography, ultrasound), (3) pulse waveform analysis approachs, and (4) calibration methods (systo-diastolic vs. approaches using brachial diastolic and mean blood pressure (BP); the latter calculated using different equations or measured by oscillometry. Methods: Invasive aortic and brachial pressure (catheterism), and non-invasive aortic and peripheral (brachial, radial) BP were simultaneously obtained (34 subjects) using different methodologies, analysis methods, measuring sites and calibration methods. SBPA and PPA were quantified. Concordance correlation and Bland-Altman analysis were done. Results: (1) In general, SBPA and PPA levels obtained with non-invasive approaches are not associated with the recorded invasively. (2) The different non-invasive approaches led to (extremely) dissimilar results. In general, non-invasive measurements underestimated SBPA and PPA; higher the invasive SBPA (or PPA), greater the underestimation. (3) None of the calibration schemes that considered non-invasive brachial BP to estimate SBPA or PPA, was clearly better over the others. (4) SBPA obtained from radial arteries waveform analysis (tonometry), were the ones that minimized mean errors. (5) PPA levels obtained from common carotid artery ultrasound recordings and brachial artery waveform analysis, were the ones that minimized the mean errors. Conclusions: Altogether the findings showed that (i) SBPA and PPA indices cannot be considered ´synonymous´, and (ii) non-invasive approaches would fail to accurately determine invasive SBPA or PPA levels, regardless of the recording site, analysis and calibration methods. Non-invasive measurements generally underestimated SBPA and PPA, and higher the invasive SBPA or PPA, higher the underestimation. There was not a calibration scheme clearly better than the others. Consequently, our study emphasizes the strong need to be critical of measurement techniques, to have methodological transparency, and the need for expert consensus for non-invasive assessment of SBPA and PPA.